Administering justice : placing the Chief Justice in American state politics - Vining, Richard L.; Wilhelm, Teena (University of Michigan Press, 2023)
Administering Justice examines the leadership role of chief justices in the American states, including how those duties require chief justices to be part of the broader state political environment. Vining and Wilhelm focus extensively on the power of chief justices as public spokespersons, legislative liaisons, and reform leaders. In contrast to much existing research on chief justices in the states, this study weighs their extrajudicial responsibilities rather than intracourt leadership. By assessing the content of State of the Judiciary remarks delivered over a period of sixty years, Vining and Wilhelm are able to analyze the reform agendas advanced by chief justices and determine what factors influence the likelihood of success. These analyses confirm that chief justices engage with state politics in meaningful ways and that reactions to their proposals are influenced by ideological congruence with other political elites and the scope of their requests. Administering Justice also examines the chief justice position as an institution, provides a collective profile of its occupants, and surveys growing diversity among court leaders.
Keywords: Judges -- United States -- States -- Powers and duties.; Judges -- United States -- States -- Leadership.; Judicial power -- United States -- States.; State courts -- United States.; Justice, Administration of -- United States -- States.; State governments -- United States.; Juges -- États-Unis -- États -- Pouvoirs et fonctions.; Juges -- États-Unis -- États -- Leadership.; Pouvoir judiciaire -- États-Unis -- États.; Cours d'État -- États-Unis.; LAW / General; Judicial power -- U.S. states; Justice, Administration of -- U.S. states; State courts; State governments; United States